Permeability properties of a large gated channel within the ferric enterobactin receptor, FepA. - Liu, J (1993)
FepA is an Escherichia coli outer membrane receptor protein for the siderophore ferric enterobactin. Prior studies conducted in vivo suggested that FepA and other TonB-dependent outer membrane proteins transport ligands by a gated-channel mechanism. To corroborate and extend these findings we have determined the permeability properties of the FepA channel in vitro, by measuring the diffusion rates of hydrophilic nonelectrolytes through the FepA channel in liposome swelling experiments. Like porins, the FepA deletion mutant delta RV showed a size-dependent permeability to oligosaccharides, indicating that it forms a nonspecific, hydrophilic pore. Unlike OmpF and other E. coli porins, however, delta RV proteoliposomes transported stachyose (666 Da) and ferrichrome (740 Da). These data, and other uptake results with a series of maltodextrins of increasing size, confirm the existence of a channel domain within FepA that is considerably larger than OmpF-type pores. These results represent a reconstitution of the channel function of a TonB-dependent receptor protein and establish that FepA contains the largest channel that has been characterized in the E. coli outer membrane.